Respostas

  • Usuário do Brainly
2014-08-14T00:40:54-03:00
I3x+1I=6

(3x+1) = ± 6

3x+1=6                      3x+1=-6
3x=6-1                        3x=-6-1
3x=5                            3x=-7
x=5/3                            x=-7/3

S={ -7/3 , 5/3 }
A melhor resposta!
  • Usuário do Brainly
2014-08-14T00:40:56-03:00
|3x+1| = 6

Temos que analisar 2 casos:

caso 1
3x+1 = 6

caso 2
3x+1 = -6

resolvendo caso 1 

3x = 6-1
3x=5
x=5/3

resolvendo caso 3

3x+1=-6
3x=-6-1
x= -7/3

Resposta S: { -7,3 e 5/3 }



1 5 1